Comprehensive Trauma-Informed Care for the Whole Community: The Whole Child Initiative Model - Gregory J. Benner Ph.D. (Educational Considerations, 2019)
The Whole Child Initiative (WCI) is a decade-long blueprint for sustainable and comprehensive community-wide change. To be successful, community-wide sustainable change must embrace a common vision, language, and common experiences to bridge the contrasting community structures, environments, and scopes of work. The Whole Child Initiative uses data, shared goals, and aligned supports ensure that every youth is safe, supported, engaged, healthy, and challenged in the community-at-large. We make the case that a population health or public health approach is needed to sustainable change in communities and the WCI model is described. Among other important outcomes, researchers have found social and emotional health of youth significantly improves across the community using the WCI approach.
Keywords: trauma; emotional and behavioral disorders; whole child; systemic change; school transformation; community transformation